2001
DOI: 10.1128/iai.69.7.4248-4256.2001
|View full text |Cite
|
Sign up to set email alerts
|

S-Fimbria-Encoding Determinant sfa I Is Located on Pathogenicity Island III 536 of Uropathogenic Escherichia coli Strain 536

Abstract: The sfa I determinant encoding the S-fimbrial adhesin of uropathogenic Escherichia coli strains was found to be located on a pathogenicity island of uropathogenic E. coli strain 536. This pathogenicity island, designated PAI III 536 , is located at 5.6 min of the E. coli chromosome and covers a region of at least 37 kb between the tRNA locus thrW and yagU. As far as it has been determined, PAI III 536 also contains genes which code for components of a putative enterochelin siderophore system of E. coli and Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 61 publications
7
90
2
3
Order By: Relevance
“…In contrast to the present study, PAI IIJ96 and PAI I536 were detected at a relatively high frequency, and PAI III536 showed the lowest frequency in UPEC strains and was not detected in commensal isolates [14]. Dobrindt et al reported that PAI III536 was more common than PAI II536 or PAI I536 in UPEC strains, including isolates from women with chronic UTIs, in contrast with our UPEC isolates from patients without catheters [11]. In other reports [20], PAI III536 and PAI II536 were reported as unstable PAIs, which could be the reason for the difference between our results and Sabate et al's findings.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In contrast to the present study, PAI IIJ96 and PAI I536 were detected at a relatively high frequency, and PAI III536 showed the lowest frequency in UPEC strains and was not detected in commensal isolates [14]. Dobrindt et al reported that PAI III536 was more common than PAI II536 or PAI I536 in UPEC strains, including isolates from women with chronic UTIs, in contrast with our UPEC isolates from patients without catheters [11]. In other reports [20], PAI III536 and PAI II536 were reported as unstable PAIs, which could be the reason for the difference between our results and Sabate et al's findings.…”
Section: Discussioncontrasting
confidence: 53%
“…In a study by Sabate et al, PAI IV536 was found most frequently in both commensal and UPEC isolates from patients with pyelonephritis and urinary sepsis [14]. In most studies worldwide, the presence of PAI IV536 in the Enterobacteriace family is documented, and this marker is known as broad-hostrange PAI or high-pathogenicity island (HPI) [11,18,19]. Our results also showed that one UPEC isolate from patients with an implanted catheter and four UPEC isolates from patients without urinary catheters suffering from sepsis carried only PAI IV536 as a single PAI marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several of these pTJ100-related genes are known to occur in PAI of human ExPEC strains. The salmochelin operon, containing iroN, has been found in PAI III 536 along with several other genes that might be linked to avian E. coli virulence, including tsh and certain components of the ColV operon [9,10]. Therefore, future researchers will need to be aware that although these pTJ100-associated genes are widespread among APEC that they may not be plasmid-located in all APEC.…”
Section: Discussionmentioning
confidence: 99%